Age-Related Changes in a Patient With Pelizaeus-Merzbacher Disease Determined by Repeated 1H-Magnetic Resonance Spectroscopy. (February 2014) - Mori, Tatsuo; Mori, Kenji; Ito, Hiromichi; Goji, Aya; Miyazaki, Masahito; Harada, Masafumi; Kurosawa, Kenji; Kagami, Shoji
A boy with Pelizaeus-Merzbacher disease underwent repeated evaluations by 3-Tesla 1 H-magnetic resonance spectroscopy (MRS). The patient showed overlap of the PLP1. Individuals selected as normal controls for 1 H-magnetic resonance spectroscopy consisted of healthy age-matched children. For 1 H-magnetic resonance spectroscopy, the center of a voxel was positioned in the right parietal lobe. 1 H-magnetic resonance spectroscopy was performed when the patient was 2, 6, 14, and 25 months old. γ-Aminobutyric acid concentration in early childhood was increased compared with that in normal controls. However, the γ-aminobutyric acid concentration in the Pelizaeus-Merzbacher disease patient was normalized at 14 and 25 months. No remarkable changes were observed in choline-containing compounds concentration at any time. These results suggest that the changes in metabolite concentrations during growth can reflect the pathological condition of Pelizaeus-Merzbacher disease. Furthermore, the lack of change in the choline-containing compounds concentration can be useful for differentiating Pelizaeus-Merzbacher disease from other white matter disorders.